Answer:
40
Step-by-step explanation:
Answer:
Step-by-step explanation:
3x - 4y = 13 (1)
2x + y = 5 (2)
——————
3x - 4y = 13
4(2x + y = 5) (2) times 4
——————-
3x - 4y = 13
8x + 4y = 20
——————-
11x = 33
x = 33/11
x = 3
Plug x = 3 in (2):
2(3) + y = 5
6 + y = 5
y = 5-6
y = -1
Thus, x = 3 and y = -1
I think its C but I could be wrong.
I hope this helps :)
Answer:
Step-by-step explanation:
(-8+2)/(8-8)= -6/0= undefined
its C
Step-by-step explanation:
- 2\sqrt5
this is the tan©
but you have to multiply by sqrt 5
so its become -2sqrt5/5